1993
DOI: 10.1002/ijc.2910540207
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a human gastric scirrhous carcinoma cell line in serum‐free chemically defined medium

Abstract: We have established a human gastric scirrhous carcinoma cell line (designated as HSC-43) in a serum-free chemically defined medium (CDM) without any polypeptide growth factor, from a primary tumor of a 56-year-old male patient. HSC-43 cells grew in vitro in adherence with a population doubling time of 55 hr, and had the cytological properties of mucinous epithelial tumor cells. Cytogenetic analysis of the cells revealed pseudotetraploidy, with structural abnormalities of deletion at chromosome Iq25 and with 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…Human diffuse-type gastric carcinoma cells were cultured as shown in Supplementary Table S1 (Takemura et al, 2004;Yashiro et al, 2009;Yanagihara et al, 1993). Lentivirus vectors were used to generate 2MLN-dnTbRII and control 2MLN-GFP cells as described .…”
Section: Cell Culturementioning
confidence: 99%
“…Human diffuse-type gastric carcinoma cells were cultured as shown in Supplementary Table S1 (Takemura et al, 2004;Yashiro et al, 2009;Yanagihara et al, 1993). Lentivirus vectors were used to generate 2MLN-dnTbRII and control 2MLN-GFP cells as described .…”
Section: Cell Culturementioning
confidence: 99%
“…A large bank of cultured cell lines reflecting this diversity of tumor phenotypes may thus be necessary to elucidate underlying mechanisms. Establishment of gastric epithelial cell lines, however, is limited by culturing difficulties and while some have been obtained from human stomach carcinomas, [1][2][3][4] most were derived from metastatic lesions in the peritoneal cavity, lymph node and liver and were relatively undifferentiated. Primary culture of fetal 5) and adult normal rat gastric epithelium has been used for functional studies of tissue-specific products, but no immortalized cell lines have been reported except for one from Nmethyl-N′-nitro-N-nitrosoguanidine-induced rat gastric carcinoma.…”
mentioning
confidence: 99%
“…The sources of the other stomach cancer cell lines established before have been described previously. [10][11][12] This study was conducted in accordance with the Declaration of Helsinki. Informed consent was obtained from all of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…The morphology of the cells was similar to that of the signet-ring cell carcinoma cell lines described previously. [10][11][12] The HSC-57 line exhibited typical morphologic features of epithelial cells, characterized by sheets of polygonal cells in a pavement-like arrangement (Fig. 1E).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation